PKM Masterplan Kawasan Wisata Pantai Dunu, Kecamatan Monano, Kab. Gorontalo Utara: (Masterplan of Dunu beach tourism area in Monano sub district, North Gorontalo district ) - Fendy Faizal Gobel; Sartan Nento; Nurnaningsih Utiarahman; Abd Syukri Entengo; Ningka Akuba (Sam Ratulangi University, 2024)
Dunu Village has a beach, which is one of the best marine destinations in North Gorontalo Regency. One of the village government's efforts to maximize this potential is by protecting the quality of its marine resources, which are the basis for developing tourism areas. Even though this beach has been used as a leading tourist attraction in North Gorontalo Regency since 2011, the Dunu beach tourist area is considered less developed as a tourism area that offers beach tourism attractions. Dunu Beach tourism still lacks supporting facilities, good facilities, and infrastructure such as road access to tourist attractions, no amenities in the form of cottages, minimal public facilities, and no beach safety boundaries to support tourist activities at Dunu Beach. The main objective of this activity is to create a Masterplan document that includes concepts, recommendations, and preparation of plans so that the area remains a destination that tourists can visit. Partners are also given socialization and training regarding making working drawings and preparing a Cost Budget Plan (RAB). This service activity started in August and was carried out in stages and continuously until a Masterplan document for the Dunu Beach tourist area was obtained. The implementation methods that will be applied in this service program are observation of existing infrastructure in coastal tourist areas, training in creating DED, RAB, and Tourism Area Management, assistance, and evaluation of aspects of structuring tourist areas. The result of this program is a master plan document for the Dunu Beach tourist area. Another target is expected to increase the partners' knowledge and the Dunu village community's knowledge and expertise in understanding working drawings and RAB as part of the master plan product in developing and structuring coastal areas. Dunu village; tourisme areas; Masterplan; Preparing a budget plan; Working Drawings. ABSTRAK Desa Dunu memiliki pantai yang menjadi salah satu destinasi bahari terbaik yang ada di Kabupaten Gorontalo Utara. Salah satu upaya pemerintah desa memaksimalkan potensi tersebut adalah dengan memproteksi kualitas sumber daya lautnya yang menjadi basis pengembangan kawasan pariwisata. Meskipun pantai ini sudah dijadikan sebagai wisata unggulan Kabupaten Gorontalo Utara sejak tahun 2011, kawasan wisata pantai Dunu justru dianggap kurang berkembang sebagaiman kawasan pariwisata yang menawarkan daya tarik wisata pantai. Wisata Pantai Dunu masih kekurangan fasilitas pendukung, sarana dan prasarana yang baik seperti akses jalan menuju objek wisata, tidak adanya amenitas berupa cottage, minimnya fasilitas umum, dan tidak adanya batas pengaman pantai untuk menopang kegiatan wisata yang ada di Pantai Dunu. Tujuan utama dari kegiatan ini adalah membuat dokumen Masterplan yang didalamnya terturang konsep, rekomendasi dan rencana penataan agar kawasan tersebut tetap menjadi destinasi yang dapat dikunjungi wisatawan. Selain itu, mitra diberikan sosialisasi dan pelatihan tentang pembuatan gambar kerja dan penyusunan Rencana Anggaran Biaya (RAB). Kegiatan pengabdian ini dimulai dari bulan Agustus dan dilaksanakan secara bertahap dan berkesinambungan sampai diperoleh suatu dokumen Masterplan kawasan wisata pantai Dunu. Adapun metode pelaksanaan yang akan diterapkan pada program pengabdian ini yaitu observasi infrastruktur eksisting di kawasan wisata pantai, pelatihan membuat DED, RAB dan Manajemen Pengelolaan Kawasan Wisata, pendampingan dan evaluasi terhadap aspek-aspek penataan kawasan wisata sehingga. Hasil dari program ini adalah adanya dokumen Masterplan kawasan wisata pantai Dunu. Target lainnya diharapkan dapat meningkatkan pengetahuan mitra dan masyarakat desa Dunu baik dalam hal keilmuan maupun keahlian dalam memahami gambar kerja dan RAB sebagai bagian dari produk masterplan dalam pengembangan dan penataan kawasan pantai.